The future of critical theory between reason and power: Reply to Amy Allen. (February 2014) - Bankovsky, Miriam
Amy Allen presents Adorno's and Horkheimer's Dialectic of Enlightenment as a productive movement between a commitment to the project of reason and a sensitivity to the effects on reason of power and domination. Agreeing with the thrust of her paper, my response considers two questions that Allen's paper opens up. The first asks how individuals might seek emancipation through reason, knowing that their reason cannot transcend contexts of power. The second asks how best to practise critical theory, given that its analyses and categories cannot rid themselves of contexts of domination. To the first, I answer that Allen's account of creative individual effort needs to be supplemented by the cultivation of an accommodating and welcoming culture, marked by the sorts of civic attitudes that Derrida and Habermas bring to their maturing relationship. Regarding the second, I extend Allen's hopes for a post-Habermasian phase of critical theory, indicating four resources in contemporary French philosophy for its further development.